Cuantificación de los desechos sólidos de la producción bananera en el cantón El Guabo - Reyes Pintado, Fernanda Gabriela (2013)
In the Canton El Guabo province of El Oro, was conducted to quantify the solid waste of banana production, with the following objectives: 1. Identify farms that produce more waste, 2. Determine the amount of solid waste in selected banana in canton El Guabo by a computer record for matrizarlo 3. Recommend a plan for the use of waste; randomly selected farms of organic bananas and conventional banana producers for six months was made weekly visits, in order to obtain information concerning the processing Fruit and evaluate biodegradable organic waste and plastics that were generated after the procedure, among the studied variables is cultivated hectares, number of bunches harvested per week; volume of non-degradable waste like sleeves, protectors, neckties, belts, sunchos, among others rachis weight after trimming, discarded fruit volume, and boxes exported class and second class in the case that this type of boxes processed, recording in each case the amount to project for a year activity. Vegetable waste organic banana plantations are less bulky and are generally below the standard, no more than 96% of nylon, polyethylene, plastic suncho, which are removed and sold to commercial Dedicated recycling. Despite corporate policy to avoid contamination, field residues are incorporated into the soil and small amounts that accumulate progressively. The few alternatives to reduce pollution from organic wastes using the technique of composting, worm humus.